China-Portugal economic relations: analysis and prospects in the context of the Belt and Road Initiative - Díaz Romero, Roger António Fretes (2018)
In 2013, the People’s Republic of China (PRC) launched a new initiative that is currently referred to as the “Belt and Road” (B&R) initiative. It aims to establish new physical, political, commercial and cultural links across Eurasia. The “Belt” refers to the “Silk Road Economic Belt” a recreation of the land-based trade connections from China throughout Eurasia. The “Road” refers to the “21st Century Maritime Silk Road”, a set or maritime routes that initially aims to extend over the South China Sea, the Strait of Malacca, the Arabic Sea and the Mediterranean Sea. Portugal is within the countries of reach of the project, although B&R is still in a very early stage for Portugal, with few explicit projects to link it with. This thesis aims to use three schools of IR theory (Realism, Liberalism and Constructivism) as its theoretical basis with the objective to link it with China-Portugal economic relations in the context of the B&R initiative. For that, we propose a research with quantitative data on Chinese trade, foreign investment and enterprise investment in Portugal. We also offer qualitative data in the form of interviews to have relevant insights in the prospects of China-Portugal relations. At the end, the goal is to link theoretical insights and the panorama of China-Portugal economic relations with the context of the overall B&R project.